Coagulation studies on „Reptilase”, an extract of the venom from Bothrops jararaca - Blombäck, Birger; Blombäck, Margareta; Nilsson, Inga Marie (Thrombosis and Haemostasis, 1957)
Reptilase — the clot-promoting extract of the venom of Bothrops jararaca — was found to have a thrombin-like activity. No effect could be demonstrated in the first phase of coagulation. Unlike bovine thrombin it was not inactivated by heparin + heparin-cofactor or by the antithrombin of normal plasma. Analyses of N-terminal aminoacids in the fibrin formed by Reptilase revealed the same aminoacids as in the fibrin formed by bovine thrombin. Quantitative differences found may reflect different specificity of the two enzymes.It is concluded that the use of Reptilase as a haemostaticum is unwarranted.We wish to thank Professor Erik Jorpes for valuable advice and support in this investigation.